PERANCANGAN LOGO RUMAH BERSALIN MEGA RAUDHAH BATU SANGKAR - Derry Ramdani, Ir. Drs. Heldi, M.Si, Dra. Zubaidah, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
The purpose of the maternity home logo design is to make maternity home identity, making the logo as a means of promoting maternity homes in order to be more developed, and for the maternity House Mega Raudhah mengeksistensikan to make it more notable. The birthing House Mega Raudhah maternity home is one that is big enough in the way of Malana, Rizano housing complex. On 10 May 2006, the maternity House was founded by the mother Hj. Megawarni Amd area Keb Jak. The birthing House provides consulting services on health and labor. Promotions conducted by the maternity home was not an objective so as not to reach a target audience that is needed, and more enjoyed by the clients prior to his labor in the maternity home, so only a handful of people who know, for that is the need for media promotion that could reach the market through the media which is quite influential in the life of the community these last few years Batusangkar. The use of the theory is a theory used in logos, visual communication design theory, theory of the layout. The analysis used are analysis of 5W1H to explain what, where, when, who, and why. The concept was used in the design of the logo of the birthing House Mega Raudhah is the silhouette of a mother and child. Mother and son is the initial idea designing maternity home Mega Raudhah logo. The Logo is a solution of a very good promotion in maternity homes, as visualization and imagery from the maternity home.Keywords: Design, home Birthing Mega Raudhah, Logo